Hearing-in-noise: comparison of listeners with normal and (aided) impaired hearing. - Bentler RA; Palmer C; Dittberner AB (Journal of the American Academy of Audiology, 2004)
In this study, the performance of 48 listeners with normal hearing was compared to the performance of 46 listeners with documented hearing loss. Various conditions of directional and omnidirectional hearing aid use were studied. The results indicated that when the noise around a listener was stationary, a first- or second-order directional microphone allowed a group of hearing-impaired listeners with mild-to-moderate, bilateral, sensorineural hearing loss to perform similarly to normal hearing listeners on a speech-in-noise task (i.e., they required the same signal-to-noise ratio to achieve 50% understanding). When the noise source was moving around the listener, only the second-order (three-microphone) system set to an adaptive directional response (where the polar pattern changes due to the change in noise location) allowed a group of hearing-impaired individuals with mild-to-moderate sensorineural hearing loss to perform similarly to young, normal-hearing individuals.